Immediate delivery or expectant management in gestational diabetes at term: the GINEXMAL randomised controlled trial. (4th November 2016) - Alberico, S; Erenbourg, A; Hod, M; Yogev, Y; Hadar, E; Neri, F; Ronfani, L; Maso, G; ,
Abstract : Objective: To evaluate maternal and perinatal outcomes after induction of labour versus expectant management in pregnant women with gestational diabetes at term. Design: Multicentre open‐label randomised controlled trial. Setting: Eight teaching hospitals in Italy, Slovenia, and Israel. Sample: Singleton pregnancy, diagnosed with gestational diabetes by the International Association of Diabetes and Pregnancy Study Groups criteria (IADPSGC), between 38 +0 and 39 +0 weeks of gestation, without other maternal or fetal conditions. Methods: Patients were randomly assigned to induction of labour or expectant management and intensive follow‐up. Data were analysed by 'intention to treat'. Main outcome measures: The primary outcome was incidence of caesarean section. Secondary outcomes were maternal and perinatal mortality and morbidity. Results: A total of 425 women were randomised to the study groups. The incidence of caesarean section was 12.6% in the induction group versus 11.7% in the expectant group. No difference was found between the two groups (relative risk, RR 1.06; 95% confidence interval, 95% CI 0.64–1.77; P = 0.81). The incidence of non‐spontaneous delivery, either by caesarean section or by operative vaginal delivery, was 21.0 and 22.3%, respectively (RR 0.94; 95% CI 0.66–1.36; P = 0.76). Neither maternal nor fetal deaths occurred. The few cases of shoulder dystocia were solved without any significant birth trauma. Conclusions: In women with gestational diabetes, without other maternal or fetal conditions, no difference was detected in birth outcomes regardless of the approach used (i.e. active versus expectant management). Although the study was underpowered, the magnitude of the between‐group difference was very small and without clinical relevance. Tweetable abstract: Immediate delivery or expectant management in gestational diabetes at term? Tweetable abstract: Immediate delivery or expectant management in gestational diabetes at term?